Numerical simulation of annular flow boiling in microchannels. (March 2016) - Guo, Z; Haynes, BS; Fletcher, DF
Flow boiling in microchannels has been researched for decades due to its potential for heat transfer applications in micro structured devices. The large number of existing experimental datasets and fitted correlations show considerable scatter and lack a mechanistic basis. The computational fluid dynamics (CFD) model developed here applies to boiling in the annular flow regime and provides insights into the underlying behaviour. Analysis of the heat transfer augmentation by interfacial waves is studied. Parametric investigations are performed using the model to understand the impact of important flow and system parameters. The calculated heat transfer coefficients are consistent with those from existing correlations, showing no more scatter than the data used to create them.